SENANDUNG BERTELUR KAU SINANGIN PADA MASYARAKAT MELAYU DI KOTA TANJUNGBALAI (STUDI TERHADAP BENTUK MUSIK, FUNGSI DAN MAKNA) - Anshor, Arrini Shabrina (Grenek: Jurnal Seni Musik, 2017)
This study aims to find out about the musical forms You Sinangin laying humming,humming to determine the function of laying You Sinangin, and to know themeaning of chanting laying You Sinangin the Malay community in Tanjungbalai.The theory used in this study includes the understanding of music, musical forms,music functions, and the theory of meaning. The method in this study using aqualitative description. Data collection techniques used were interviewsobservation and documentation are made directly to pesinandong in Tanjungbalai.The population in this study is adatyang figure amounted to 4 people consisting of3 players Gubang musical instruments, and 1 person pesinandong. Results ofresearch and interviews show that this form of music in hum laying You Sinaginhas 7 motif in the 10 phrase, namely 5 phrases antecedent (question) and 5 phrasesconsequent (answer) and there are 5 sentence is a sentence I, sentence II, sentenceIII, sentence IV, and V. sentence humming laying function as accompaniment YouSinangin ceremony, an emotional disclosure functions and entertainment functions.And the meaning tekandung in humming laying You Sinangin consists of a feelingof meaning, the meaning of the tone and meaning of the goal.